Case Series of Dengue Fever in Peripartum Period: Maternal and Foetal Outcome - Yudianto Budi Saroyo; Ali Sungkar; Rima Irwinda; Raymond Surya (MDPI AG, 2020)
Introduction: Dengue fever is a major public health problem in tropical and subtropical areas. There are not many studies concerning the complications of dengue fever in pregnancy. We present four serial cases of dengue fever in pregnancy. Case illustration: Three of four cases were delivered by caesarean section; two of them died during post-caesarean care. All cases had the lowest platelet level below 50,000/µL and were given platelet transfusion during and after delivery; they also showed abnormal liver function tests. For foetal outcome, none tested positive for dengue. Discussion: Complication of dengue infection depends on a combination of host and viral virulence. Regardless of prophylactic platelet transfusion, some studies revealed clinical bleeding in patients with dengue infection due to an intricate effect on the haemostatic system. The adverse foetal outcome may contribute because of placental circulation caused by endothelial damage with increased vascular permeability leading to plasma leakage. There is no national guideline for dengue fever in pregnancy. Conclusions: The management of dengue fever in pregnancy at the tertiary hospital is still suboptimal. Dengue fever around peripartum presents a higher risk of morbidity and mortality for the mother and therefore needs a multidiscipline team approach.